Korporativna obveščevalna dejavnost: Praktikum - Dvojmoč, Miha (University of Maribor Press, 2026)
Corporate Intelligence: Practicum. Corporate intelligence could represent a tool for increasing awareness of modern organizations that want to operate safely, especially from the perspective of global business, taking into account risks in the market, as well as opportunities for their own competitive development. As a tool for managing challenges and upgrading operations from the perspective of competitiveness and security in the market, the awareness of the necessity of corporate security in modern global business represents an inevitable step towards competitive and secure global business, with awareness of external risks, exploitation of own advantages and knowledge of market characteristics. In general, corporate intelligence improves the functioning of organizations; gains competitive advantage; manages risks; protects the entire organization; enables faster and more comprehensive decisions and ensures sustainable development of the organization.